Integrated miRNA-mRNA analysis in the habenula nuclei of mice intravenously self-administering nicotine - Lee, Sangjoon; Woo, Jiwan; Kim, Yong Sik; Im, Heh-In (NATURE RESEARCH, 2015)
A considerable amount of evidence suggests that microRNAs (miRNAs) play crucial roles in the neuroadaptation of drug addiction. Habenula (Hb), one of the critical brain regions involved in reward and addiction, can be divided into two anatomically and transcriptionally distinct regions: medial habenula (MHb) and lateral habenula (LHb) nuclei. However, very few studies have compared the functional roles of these regions. Here, by using mirConnX integrator and KEGG pathway mapping, we simultaneously analysed the differential expression patterns of miRNAs and messenger RNA (mRNA) within MHb and LHb under nicotine addiction. Significantly altered miRNAs and mRNAs were found in the Hb of mice intravenously self-administering nicotine. Interestingly, some miRNAs were oppositely regulated between the MHb and the LHb, and their potential targets included various genes of cell signalling pathways related to the degeneration of fasciculus retroflexus (FR). This study provides an improved insight into the differential regulation of habenular transcripts in nicotine addiction, as well as the potential functions of miRNAs in several biological pathways involved in the nicotine addiction.
Keywords: CUE-INDUCED REINSTATEMENT; FUNCTIONAL-ANALYSIS; GABAERGIC NEURONS; LATERAL HABENULA; MEDIAL HABENULA; ACETYLCHOLINE; RECEPTOR; NEUROTROPHIN; BRAIN; DEGENERATION